2003
DOI: 10.1348/026151003765264048
|View full text |Cite
|
Sign up to set email alerts
|

The development of national in‐group bias: English children's attributions of characteristics to English, American and German people

Abstract: This study investigated the development of national ingroup bias in 5-11-year-old children. Three hundred and seven English children were asked to attribute characteristics to their own national group either on its own or in conjunction with attributing characteristics to one of two national outgroups, either Americans or Germans. The importance which the children ascribed to their own national identity in relationship to their other social identities was also assessed. It was found that, with increasing age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 42 publications
4
36
2
3
Order By: Relevance
“…Second, Gardham and Brown (2001) suggest that recategorization becomes more difficult if contextual cues exist which highlight the salience of the original categories (i.e., 'British,' 'German'). Significantly, previous research suggests that amongst children there exists a context of a salient intergroup rivalry between Germany and Britain (see Abrams et al, 2003a;Barrett, et al, 2003;Rutland, 1999Rutland, , 2004, which may well discourage the recategorization process. Nonetheless, future research should investigate whether the recategorization account may help explain the development of the PNAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Gardham and Brown (2001) suggest that recategorization becomes more difficult if contextual cues exist which highlight the salience of the original categories (i.e., 'British,' 'German'). Significantly, previous research suggests that amongst children there exists a context of a salient intergroup rivalry between Germany and Britain (see Abrams et al, 2003a;Barrett, et al, 2003;Rutland, 1999Rutland, , 2004, which may well discourage the recategorization process. Nonetheless, future research should investigate whether the recategorization account may help explain the development of the PNAE.…”
Section: Discussionmentioning
confidence: 99%
“…However, significantly they did not inhibit their explicit bias, rather heightened public self-focus only acted to increase national ingroup bias. This suggests that while early adolescents may be aware of a generic or moral norm against discrimination their intergroup attitudes, in the context of a salient intergroup rivalry between Germany and Britain (see Abrams et al, 2003a;Barrett, Wilson, & Lyons, 2003;Rutland, 1999Rutland, , 2004, may be affected by a specific ideological or social-conventional norm that legitimizes national intergroup bias (Amiot & Bourhis, 2003, 2005aKillen & Stangor, 2001;Rutland, 1999).…”
mentioning
confidence: 99%
“…Therefore, most of the respondents were age 11 (about 49 per cent) or 12 (about 36 per cent) in 2009. It should be noted that psychological research points out that this period is decisive for developing a national identity (Barrett, Wilson and Lyons 2003). Given the high multicollinearity between age and grade (Cramer's V00.64; pB0.000), we had to choose between one of these two variables to enter the model.…”
Section: Ethnic School Context 365mentioning
confidence: 99%
“…That said, while English children's attitudes towards Germans are usually significantly less positive than their attitudes towards any other national outgroup, German peoples are not always described with predominantly negative characteristics, suggesting that English children tend to hold representations of Germans which are neutral rather than negative overall (see Barrett & Short, 1992;Barrett et al, 2003). Indeed, in a recent study which included English 6-, 9-, 12-and 15-year-olds, Barrett (2007) found that, at all four ages, there were no significant differences in the number of negative and positive attributes ascribed to German people by these children, suggesting a neutral rather than a negative evaluation of German people overall.…”
Section: Introductionmentioning
confidence: 99%